HUBUNGAN PENGETAHUAN KESEHATAN REPRODUKSI REMAJA TERHADAP PERILAKU REPRODUKSI SEHAT PADA REMAJA PUTRI DI DESA PARTIHAMAN SAROHA KECAMATAN KOTA PADANGSIDIMPUAN TAHUN 2016 - Harahap, Aprilda; Pohan, Rostina Aprina (Universitas Aufa Royhan, 2018)
This research works through to hit health adolescent reproduction which is a sejahtera'ssituation physical, mental, and whole ala social doesn't particularly free of disease or disablement ina thing that gets bearing with system reproduces, function and its process. health Reproduces at thismature Indonesia stills haven't as one be expected. To the effect of observational it to know howhealths gnostic relationship reproduce stripling to healthy reproduction behaviour on adolescentdaughter at Silvan Partihaman Saroha Padangsidimpuan Hutaimbaru's district this2016.Penelitian's Year utilize descriptive research design kolerasi with approaching cross secsional .Sample represents all population, which is Daughter Stripling At Silvan Partihaman SarohaPadangsidimpuan Hutaimbaru's district Year 2016. Of 50 enough knowledgeable Majorityrespondents 12 person (42%) one that does as much 4 person (8%) and that doesn't do as much 17person (34%), and knowledgeable The Few good as much 13 person (26%) one that does 7 person(14%) and that doesn't do total 6 person (12%). Base table upon utilized by quiz Exact fisher’ s.Usufruct acquired quiz points out that P = 0,002 it means that P < 0,05. Concluded availablerelationship which signifikan among gnostic health reproduces stripling with behavioural healthyreproduction at silvan Partihaman Saroha Padangsidimpuan Hutaimbaru's districtPadangsidimpuan's city year 2016. Expected to daughter Stripling to follow counselling of on duty health and also another health officer and looks for information about Reproduction health and healthy reproduction Behaviour.